Evaluasi Usability E-Commerce yang Terintegrasi dengan Fan Community Platform Menggunakan Metode Cognitive Walkthrough - Khalisatifa, Aida; Ibrahim, Ali (Politeknik Negeri Batam, 2025)
This study aims to evaluate the usability and user experience of Weverse Shop e-commerce app after integration into Weverse app using the Cognitive Walkthrough and Post Study System Usability Questionnaire (PSSUQ) methods. Cognitive Walkthrough is used to identify usability issues from an expert perspective, while PSSUQ is used to quantitatively measure user experience through three subscales: System Usefulness, Information Quality, and Interface Quality. Participants in this study ran 7 task scenarios relevant to the application features. Based on the analysis results, the average scores for the PSSUQ subscales were 2.99 for System Usefulness, 2.98 for Information Quality, and 2.87 for Interface Quality, with an overall score of 2.95. These results indicate that the application interface still needs improvement, especially in the aspects of navigation and information delivery. This research provides recommendations for improvements to usability elements to increase user satisfaction.